Histochemistry of the zona pellucida of the ovary of a species with natural polyovulation: Lagostomus maximus (Rodentia, Hystricomorpha, Chinchillidae) - Acuña, Francisco (2019)
This study reports the histochemistry and the distribution of glycoconjugates (GCs) in the zona pellucida (ZP) of preantral, secondary, tertiary, polyovulatory and atretic follicles of ovaries from non-pregnant (NPr) and pregnant (Pr) females of Lagostomus maximus. GCs were studied using histochemical and lectin histochemical methods. The viscacha ZP was positive to all the histochemical techniques. In addition, it was observed that the intensity of staining of the ZP was constant in the different follicular stages between both female groups. The lectin histochemical study revealed that ZP was positive for certain lectins (WGA, RCA-I and CON-A) and that the labelling did not vary between the different follicular stages, but between the two groups of females. By using both histochemical techniques, it was established that the GCs present in the ZP label the complexity of the area. These results allow us to increase our knowledge on the biology of the viscacha's ovary, particularly contributing to the study of polyovulation.